Minimally invasive treatment of vesicourethral leak after laparoscopic radical prostatectomy - ELMOR,TIAGO RIVELLO (2016)
ABSTRACT Objective: to describe our experience with a minimally invasive approach for persistent vesicourethral anastomotic leak (PVAL) after Laparoscopic Radical Prostatectomy (LRP). Methods: from 2004 to 2011, two surgeons performed LRP in 620 patients. Ten patients had PVAL, with initially indicated conservative treatment, to no avail. These patients underwent a minimally invasive operation, consisting of an endoscopically insertion of two ureteral catheters to direct urine flow, fixed to a new urethral catheter. We maintained the ureteral catheters for seven days on average to complete resolution of urine leakage. The urethral catheter was removed after three weeks of surgery. Results: the correction of urine leakage occurred within a range of one to three days, in all ten patients, without complications. There were no stenosis of the bladder neck and urinary incontinence on long-term follow-up. Conclusion: the study showed that PVAL after laparoscopic radical prostatectomy can be treated endoscopically with safety and excellent results.